Redefining Psychiatry Placements: Improving Medical Education Through the UTLA Scheme - Sanaa Moledina; Hetal Acharya (BJPsych Open)
Aims: Psychiatry placements can be challenging for medical students due to unpredictable settings, emotionally charged patient interactions, and potential risks. Limited hands-on experience, inadequate supervision, inconsistent teaching across the wards, and poor induction further amplify students’ apprehensions, reduce engagement, and deter them from considering a career in psychiatry. To address these challenges, the University of Leicester Medical School (LMS) initiated the Undergraduate Teaching Liaison Associates (UTLA) scheme within Northamptonshire Healthcare NHS Foundation Trust to improve medical education in the mental health sector. This programme, grounded in the Near-Peer Teaching model, provides structured mentorship and personalized guidance to medical students. The quality improvement project focused on implementing and adapting the UTLA initiative specifically for psychiatry placements.